2001
DOI: 10.1111/0824-7935.00133
|View full text |Cite
|
Sign up to set email alerts
|

Wishful: A Discourse Planning System That Considers a User's Inferences

Abstract: The explicit consideration of an addressee's inferences during discourse planning affects the content and coherence of the generated discourse. The content of the discourse is affected because the consideration of an addressee's inferences may require the addition of information that addresses erroneous inferences or suggest the omission of easily inferred information. The coherence of the discourse is affected because the generated discourse should incorporate inferential relations that emerge from the consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In 1990-2000, explanations derived from knowledge bases were enhanced by addressing aspects of users' reasoning. Specifically, Zukerman and McConachy (1993) and Horacek (1997) considered potential inferences from explanations, omitting easily inferable information and addressing erroneous inferences; Korb et al (1997) took into account reasoning fallacies when explaining the reasoning of Bayesian Networks; and Stone (2000) generated instructions from which users could draw appropriate inferences about actions to take.…”
Section: Related Workmentioning
confidence: 99%
“…In 1990-2000, explanations derived from knowledge bases were enhanced by addressing aspects of users' reasoning. Specifically, Zukerman and McConachy (1993) and Horacek (1997) considered potential inferences from explanations, omitting easily inferable information and addressing erroneous inferences; Korb et al (1997) took into account reasoning fallacies when explaining the reasoning of Bayesian Networks; and Stone (2000) generated instructions from which users could draw appropriate inferences about actions to take.…”
Section: Related Workmentioning
confidence: 99%
“…The types of text generated include instruction manuals of different types (Rösner and Stede, 1992;Vander Linden and Martin, 1995;Wahlster et al, 1991), administrative forms (Not and Stock, 1994), user documentation (Hartley and Paris, 1997), descriptions of tourist sights (Krifka-Dobes and Novak, 1993), and descriptions of concepts (Zukerman and McConachy, 2001), which are all monologic discourse types. Interactive dialogue has also been addressed, mostly in instructional texts: explanatory discourse about electronic circuits (Cawsey, 1990), advisory dialogues (Moore and Paris, 1993), and dialogue interaction with a database (Fischer et al, 1994).…”
Section: Areas Of Applicationmentioning
confidence: 99%
“…The research reported by Joshi et al (1984), van Beek (1987 and Zukerman and McConachy (2001)) considers the addition of information to planned discourse to prevent or weaken a user's erroneous inferences from this discourse. Our mechanism for adding explanatory extensions to an interpretation prevents inferences that people find objectionable due to jumps in belief.…”
Section: Related Researchmentioning
confidence: 99%